Olfactory event-related potentials in a functionally anosmic patient with arrested hydrocephalus - Caminiti, Fabrizia (J Int Med Res, 2019)
Hydrocephalus is one of the lesser known causes of central olfactory loss. The pathogenesis of hydrocephalus involves the olfactory bulbs or tracts, and more rarely, other frontotemporal cortical regions. We describe a case of olfactory dysfunction in a macrocephalic 63-year-old female patient with arrested hydrocephalus. Her olfactory function was assessed by using the Sniffin’ Sticks test, olfactory event-related potentials (OERPs), and 3-Tesla magnetic resonance imaging (MRI). An OERP examination suggested partial impairment of the central olfactory pathways and central parietal regions where OERP amplitude is maximal. Indeed, we found an evident olfactory potential trace with an increased latency only on Pz derivation. However, structural MRI showed important cortical brain thinning and large expansion of the third ventricle, with evident damage of the olfactory frontotemporal areas. The Sniffin’ Sticks test and MRI supported the diagnosis of anosmia, while OERP findings indicated partial preservation of olfactory function, likely due to an adaptation of the central olfactory system. These findings highlight the importance of a multi-integrated approach to detect olfactory impairment.